Use of velvet bean and vermicompost as organic fertilizer for lettuce in Mozambique (Research, Society and Development, 2023)
The search for fertilizers economically viable for family farmer, such as organic fertilizers, which are cheap sources of nutrients, and that preserve the physical, chemical and biological properties of the soil, is an important strategy for emerging countries, such as Mozambique, to increase the income of their population. The objective of this paper was to evaluate the potential of organic fertilizers (velvet bean and vermicompost) on the yield of lettuce. An experiment under field conditions was conducted in Bandula, Manica province, Mozambique, in a randomized block design comprising split plots and 4 replications. The treatments consisted of the application of 0 (control); 2; 3.5 and 5 kg ha-1 of velvet bean or vermicompost in raised beds that later received lettuce seedlings with 4 to 8 leaves (cv. Alface EDEN). Growth indicators and lettuce yield were evaluated 70 days after transplanting. It was found that plants fertilized with 3.5 kg ha-1 of velvet bean were statistically superior to plants fertilized with vermicompost because they had greater plant height, head diameter, number of leaves, and fresh mass of the aerial part, which resulted in an increase of 40% in lettuce yield. Our results suggest that the fertilization of EDEN Lettuce with 3.5 kg ha-1 velvet bean represents a strategy to improve its yield in low nutrient input cropping systems.